2018
DOI: 10.1155/2018/9367034
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Morphological and Physical Properties of Different Absorbent Wound Dressings

Abstract: Good quality wound dressings should have exceptional properties for usage, such as being able to remove excess wound exudates, having rapid dehydration, and providing optimal water vapour permeability. This study evaluated and compared the morphological and physical properties of six different commercially absorbent wound dressings in Thailand: two hydrocolloids, two alginates, and two foams. These wound dressings are available in a variety of components and structures, some of which have a multilayer structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 8 publications
(14 reference statements)
0
17
0
Order By: Relevance
“…This makes them waterproof and practically impermeable to gases. 57 Hasatsri et al 58 compared the WVTRs of different dressing and showed that hydrocolloids had the lowest WVTRs. 59 Wu et al 60 studied the effect of Duo-DERM hydrocolloid dressing on the WVTRs of full-thickness burns, deep-partial thickness burns, and chronic leg ulcers.…”
Section: Water Vapor Transmission Ratementioning
confidence: 99%
“…This makes them waterproof and practically impermeable to gases. 57 Hasatsri et al 58 compared the WVTRs of different dressing and showed that hydrocolloids had the lowest WVTRs. 59 Wu et al 60 studied the effect of Duo-DERM hydrocolloid dressing on the WVTRs of full-thickness burns, deep-partial thickness burns, and chronic leg ulcers.…”
Section: Water Vapor Transmission Ratementioning
confidence: 99%
“…To calculate the WRC SA , Equation (2), WRC of starch-alginate mixtures was measured. These WRC values were higher than WRC CS , due to alginates retained relevant amounts of available water in formulations (Hasatsri et al, 2018). The WRC of commercial sodium alginates was 12.09 ± 1.08 and 10.16 ± 2.37 (g water/g d.b.)…”
Section: Water Retention Capacity (Wrc)mentioning
confidence: 79%
“…What is the ideal dressing for STSG donor sites remains debatable in the literature [ 15 ]. Alginate dressing is reported to have a high absorption capacity and high dehydration rate when compared to other types of wound dressings [ 16 - 17 ]. However, they can be painful to remove and cause higher hyperkeratosis of healed scars.…”
Section: Reviewmentioning
confidence: 99%